Telehealth Solutions for Rural Children : Bridging the Healthcare Gap - Bilal Shah; Usman Shahbaz Khan; Zain Abbas Qureshi (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Access to healthcare remains a significant challenge in rural areas, especially for children. This paper explores the role of telehealth in providing healthcare services to rural children, particularly in remote areas with limited medical infrastructure. The study examines telemedicine technologies, such as remote consultations, diagnostic tools, and health monitoring systems, and their impact on improving healthcare access and outcomes for children in underserved communities.